1996
DOI: 10.1007/bf02505232
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of filaggrin in atopic skin

Abstract: The amounts of the epidermal proteins filaggrin, involucrin, cystatin A and Ted-H-1 antigen produced during the terminal differentiation of keratinocytes were immunohistochemically measured in lesional and nonlesional skin of atopic dermatitis (AD) patients. In addition, the amount of filaggrin in the skin of the inner surface of the upper arm of AD patients (nonlesional skin) and normal controls, obtained by punch biopsy, was measured by an enzyme-linked immunosorbent assay (ELISA) technique. The immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 31 publications
6
106
0
3
Order By: Relevance
“…A breakdown product of filaggrin, natural moisturizing factor, acts in retaining moisture and further contributes to the hydration of the skin. Before the identification of filaggrin null mutations (FLG), decreased expression of filaggrin has been shown in AD (9 Since then, more than 30 independent studies worldwide have confirmed the association of FLG with AD. However, the majority of AD patients do not carry FLG.…”
Section: Filaggrin Mutations: Evidence For Physical Barrier Defects Amentioning
confidence: 99%
“…A breakdown product of filaggrin, natural moisturizing factor, acts in retaining moisture and further contributes to the hydration of the skin. Before the identification of filaggrin null mutations (FLG), decreased expression of filaggrin has been shown in AD (9 Since then, more than 30 independent studies worldwide have confirmed the association of FLG with AD. However, the majority of AD patients do not carry FLG.…”
Section: Filaggrin Mutations: Evidence For Physical Barrier Defects Amentioning
confidence: 99%
“…The well-known clinical association between IV and AD and the previously observed decrease of filaggrin expression in AD [57,58] suggested that FLG loss-of-function mutations might also be of relevance for AD. Subsequently, Palmer et al showed that both the R501X and 2282del4 alleles are strong predisposing factors for AD [59]; following this initial report an impressive series of independent replication studies (for reviews, see [55,60,61]) has provided unequivocal evidence that FLG null alleles are major risk factors for AD.…”
Section: Filaggrinmentioning
confidence: 94%
“…Recent human genetic studies strongly suggest that perturbation of the skin barrier function as a result of reduction or complete loss of filaggrin expression leads to enhanced percutaneous transfer of an allergen (47)(48)(49). The expression level of filaggrin has been known to be decreased in AD patients at both the protein and mRNA levels (50,51). The filaggrin gene defect may be the foundational predisposing factor not only for the development of eczema, but also for the initial sensitization and progression of the allergic diseases (47,48).…”
Section: Possible Evidence Of the 'Social Manner' Of Cells And Moleculesmentioning
confidence: 99%